Supportive Care Needs and Health-Related Quality of Life of Esophageal Cancer Survivors - Eunju Choi; Soo Hyun Kim; Young Whee Lee; Hwasoon Kim; Young Mog Shim; Genehee Lee; Deborah L Volker (Elsevier, 2021)
Objective: The aim of this study is (1) to describe the prevalence and correlates of unmet needs among esophageal cancer survivors (ECS) in Korea and (2) to identify the association between unmet needs and health-related quality of life (HRQOL). Methods: We used a cross-sectional descriptive study design. Participants were 118 ECS from a hospital in Korea who received surgery at least 12 months before participating. We collected data including the Supportive Care Needs Survey-short form 34 and to measure HRQOL, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 with a self-report questionnaire. Results: Participants' mean age was 65.2 years, and 92.4% were male. Among five domains of supportive care needs, unmet need prevalence ranged from 0.8% to 50%. The most commonly reported domains of unmet needs were Health System and Information and Physical and Daily Living. Participants with unmet needs in Psychological Needs, Physical and Daily Living Needs, and Patient Care and Support Needs demonstrated significantly poorer HRQOL in almost all measured domains. Conclusions: Our finding suggests that Korean ECS had substantial unmet needs, especially in the Health System and Information domain. Psychological, Patient Care and Support, and Physical and Daily Living Needs were related to HRQOL. The study can advance understanding of priority issues in ECS.